When do businesses report cybercrime? Findings from a UK study - Kemp, Steven (Criminology & criminal justice, 2023)
Although it is known that businesses report cybercrime to public authorities at a low rate, and this hinders prevention strategies, there is a lack of research on companies’ decisions to report cyber victimisation. This paper analyses the UK Cyber Security Breaches Survey to explore factors associated with cybercrime reporting by businesses. Results indicate that the type of cybercrime is relevant to the reporting decision, and that the likelihood of reporting increases when cybersecurity incidents generate negative impacts and when the company places high priority on cybersecurity. However, we find no association between having cybersecurity insurance and reporting. Finally, while having outsourced cybersecurity management is associated with reporting to anyone outside the organisation but not to public authorities, in-house cybersecurity teams seem more inclined to report to public authorities. Findings are discussed in relation to the role of the private cybersecurity sector and the criminal justice system in combatting cybercrime.